Study on Solid Phase Extraction and Spectrophotometric Determination of Gold with 5-(2-Hydroxy-4-sulfo-5- chlorophenolazo)thiorhodmine as Chromogenic Reagent - LIANG†, JINGJING; ZHAO, JISHOU; YE, YANQING; HU*†, QIUFEN; YANG†, GUANGYU (Asian Journal of Chemistry, 2009)
In this paper, a new method for the determination of gold based on the rapid reaction of gold with 5-(2-hydroxy-4-sulfo-5-chlorophenolazo) -thiorhodmine (HSCT) and the solid phase extraction of the coloured chelate with a reversed phase polymer-based C18 cartridge has been developed. In the presence of 0.05-0.5 mol L-1 of hydrochloric acid solution and emulsifier-OP medium, HSCT reacts with gold to form a red chelate of a molar ratio 1:3 (gold to HSCT). This chelate was enriched by the solid phase extraction with a polymer-based C18 cartridge and eluted the retained chelate from the cartridge with dimethyl formamide. The enrichment factor of 100 was achieved. In the DMF medium, the molar absorptivity of the chelate is 1.32 × 105 L mol-1 cm-1 at 510 nm. Beer's law is obeyed in the range of 0.01-2.0 μg mL-1 in the measured solution. The relative standard deviation for eleven replicates sample of 0.5 μg L-1 level is 2.22 %. The detection limit, based on the three times of standard deviation is 0.03 μg L-1 in the original sample.